Use cases, best practice and reporting standards for metabolomics in regulatory toxicology - Mark R. Viant (Nature Portfolio, 2019)
Lack of best practice guidelines currently limits the application of metabolomics in the regulatory sciences. Here, the MEtabolomics standaRds Initiative in Toxicology (MERIT) proposes methods and reporting standards for several important applications of metabolomics in regulatory toxicology.